Teater Pose, Adaptasi Seni Peran Teater untuk Aplikasi Pertunjukan Fesyen Naratif - Benny Yohanes Timmerman (Jurnal Kajian Seni, 2021)
The purpose of this article is to find ways and formulas to create performance models with the application of forms and expressions of body poses, in a narrative fashion performance format. The adaptation method will be applied to identify forms and expressions of theater acting that are in accordance with the concept of narrative fashion performance. This type of research combines desk-research (literature study) and field-research (phenomenon studies), resulting in the identification of a number of themes, related to the phenomenon of pose expression, especially those that develop in social media.The making of the Pose Theater model, in the form of this Narrative Fashion Performance, is carried out with a multi-theory inclusion approach, namely: Performative Body, Pose Presentation, Affect Dramaturgy, Equilibrium Narrative, Transcoding Adaptation, and Atmospheric Aesthetics.The article resulted in the formulation of applied knowledge in the form of a theater acting adaptation strategy for the application of narrative fashion performances. The performance model is a synthesis of Theater Semiotics knowledge, with a focus on studying semiotics of clothing (in fashion styles) and the creation of performative body poses, which are based on research results on the phenomenon of 'selfie' and 'TikTok' on social media. The visual form of pose theater is established through the creation of ready-to-wear fashion, as well as the arrangement of the stage atmosphere based on the adaptation of the rules of fashion-ology.The script model still applies the Aristotelian dramatic structure, intended as an act of borrowing, where this model uses materials, ideas, or forms from the previous text, namely the modeling convention in theatre. But the way of arranging the elements in each scene is a transposition where adaptation is a change from one semiotic system to another, namely from a dramatic theater system to a kinetical-visual theater system. ABSTRAKPengembangan seni teater, khususnya bidang seni peran (acting) dapat dilakukan melalui strategi inklusi (multi) teori, dan diperkaya dengan wawasan lintas disiplin sebagai rekoneksi pengetahuan. Tulisan ini akan membahas strategi inklusi teori, antara Seni Peran Teater, Semiotika Pakaian, dan Fashion-ology; yang diperkaya dengan wawasan rekoneksi keilmuan untuk menghasilkan formulasi konsep baru, yaitu Teater Pose. Tulisan ini menghasilkan rumusan konsep Teater Pose, berupa strategi kinetik-visual untuk menyampaikan unsur naratif dan semiotika busana, dan adaptasi seni peran menjadi suatu vokabuler seni pose. Pada tingkat aplikasi, konsep ini diturunkan menjadi formulasi model Pertunjukan Fesyen Naratif. Pertunjukan Fesyen Naratif dibangun oleh kekuatan kreasi pose sebagai re-kreasi seni tablo, semiotisasi gaya fesyen menjadi representasi karakter, yang konsep naratif dan mode pengisahannya dikaitkan dengan hasil riset fenomena ‘selfie’ dan ‘TikTok’ di media sosial, sebagai referensi eksternalnya.Pembuatan model skrip sebagai aplikasi dari konsep Teater Pose, menggunakan struktur dramatik Aristotelian yang klasik, dimaksudkan sebagai tindakan meminjam (borrowing), di mana model ini menggunakan bahan, gagasan atau bentuk dari teks sebelumnya, yaitu konvensi pengadeganan dalam teater. Tetapi cara menyusun unsur-unsur dalam setiap adegan merupakan  sebuah transposisi di mana adaptasi adalah perubahan dari satu sistem semiotik ke sistem semiotik lain, yakni dari sistem teater literal-dramatik menjadi sistem performatif visual-kinetik.